1997
DOI: 10.1017/s071498080001415x
|View full text |Cite
|
Sign up to set email alerts
|

Spousal Caregiving in the Institutional Setting: Task Performance

Abstract: RÉSUMÉCette étude examine le phénomène des soins donnés par l'épouse à la suite du placement en établissement de son conjoint âgé. En théorie, l'étude puise dans la perspective d'interprétation sociologique et dans le concept de carriére. Son aspect méthodologique repose sur un cadre longitudinal et prospectif et réunit les approches quantitatives et qualitatives. Les données sont tirées d'une etude plus vaste qui explorait la transition vers un état de quasi-veuvage. L'article traite d'un aspect des soins sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
1
6

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 21 publications
5
33
1
6
Order By: Relevance
“…Such support can serve to increase the caregivers' understanding of their experience and to increase their awareness of possible solutions to their problems. Ross et al (1997a) found that 9 months after admission, some wife caregivers became less involved in providing care and reported less symptoms of depression. As mentioned by these authors, excellent nursing care may assure them that their relatives are receiving appropriate care and allow them to "concentrate on other aspects of their lives rather than on the provision of care" (Ross et al, 1997a, p. 95).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such support can serve to increase the caregivers' understanding of their experience and to increase their awareness of possible solutions to their problems. Ross et al (1997a) found that 9 months after admission, some wife caregivers became less involved in providing care and reported less symptoms of depression. As mentioned by these authors, excellent nursing care may assure them that their relatives are receiving appropriate care and allow them to "concentrate on other aspects of their lives rather than on the provision of care" (Ross et al, 1997a, p. 95).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned by these authors, excellent nursing care may assure them that their relatives are receiving appropriate care and allow them to "concentrate on other aspects of their lives rather than on the provision of care" (Ross et al, 1997a, p. 95). Ross et al (1997a) also underlined that caregivers who want to remain involved with caring should be helped to do so in ways that do not compromise their psychological wellbeing. As informal support also plays an important role in relation to psychological distress, nurses could assist caregivers in strengthening their ability to seek and accept social support from their network.…”
Section: Discussionmentioning
confidence: 99%
“…During visits, families may engage in a variety of activities/tasks that provide them with a purpose. Ross, Rosenthal, and Dawson (1997) report that wives of institutionalized husbands viewed visiting as their most important task, although, they continued to perform personal, instrumental, relational and recreational care tasks. Just over one‐third of the 45 wives interviewed were heavily involved in providing emotive support and performing care tasks (Ross et al, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ross, Rosenthal, and Dawson (1997) report that wives of institutionalized husbands viewed visiting as their most important task, although, they continued to perform personal, instrumental, relational and recreational care tasks. Just over one‐third of the 45 wives interviewed were heavily involved in providing emotive support and performing care tasks (Ross et al, 1997). In another study involving spouses, visiting, talking and participating in various activities while at the facility helped to preserve marriages and familiar role relationships (Gladstone, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation